Biofate and cellular interactions of lipid nanoparticles - Baldim, Iara (2022)
By definition, drug targeting and delivery is the process of delivering a drug molecule to a specific site where the pharmacological effect is desired. A targeted release may simplify the drug administration protocols and reduce the amount of drug necessary, thus improving the cost-effectiveness and reducing the side effects. A drug administered by intravenous injection distributes in the whole body, reaching organs, tissues and cells where it's action is not required, potentially causing harmful effects. Therefore targeting is essential for the drug to reach the necessary concentration for therapeutic efficacy, while minimizing the toxic and unwanted effects to other organs caused by random and uncontrolled bioactive action. Nowadays, most of the targetable controlled drug delivery systems are based on nanotechnology. High selectivity and specificity ensure the physical contact of the bioactive molecule with the physiological target only at the desired location of the body. Indeed, the development of highly selective and site-specific delivery systems capable of maintaining the optimal effect in a suitable time frame is one of the main challenges in nanotherapy. Desirable features in nanocarriers include biodegradability and biocompatibility, nonimmunogenicity and stability in the bloodstream. These features can be found in different nanosystems available, such as liposomes, solid lipid nanoparticles (SLN) and nanostructured lipid carriers (NLC), nanogels, micelles, dendrimers, and so on. The surface area of a particulate system increases several orders of magnitude with the decrease of its size to nanometric scale, promoting higher interactions with the biological environment.